Dressing‐Controlled Quantum Steering in Energy‐Level Cascaded Parametric Amplified Four‐Wave Mixing Processes. Issue 8 (3rd July 2020) - Liu, Yuliang; Li, Kangkang; Li, Wei; Li, Sifan; Cai, Yin; Zhang, Yanpeng
Abstract: Einstein–Podolsky–Rosen (EPR) steering for multipartite systems plays an important role in several quantum technologies and applications, e.g., quantum communication and quantum metrology. In this study, an energy‐level cascaded four‐wave mixing (EC‐FWM) process modulated by the dressing effect is proposed to generate three‐ and four‐mode EPR steering in the atomic medium of rubidium. The energy‐level simultaneously cascaded FWM and the energy‐level ordinally cascaded FWM are compared in three‐mode EPR steering, and monogamy relations for Gaussian steerability are also verified. Furthermore, multipartite EPR steerability is controlled by actively adjusting the dressing field. Different types of EPR steerability exhibit different modulation results when the dressing conditions of enhancement and suppression are satisfied. The proposed scheme exhibits advantages such as scalability, flexibility, and simplified experimental setup and can construct controllable large‐scale quantum networks. Abstract : An energy‐level cascaded four‐wave mixing process modulated by the dressing effect is proposed to generate multimode Einstein–Podolsky–Rosen (EPR) steering in rubidium atomic medium. Monogamy relations are verified and multipartite EPR steerability is controlled by adjusting the dressing field. Different types of EPR steerability exhibit different modulation results when the dressing conditions of enhancement and suppression are satisfied.